Thymic Polypeptide Fraction Biomodulina T Decreases Exhausted and Terminally Differentiated EMRA T Cells in Advanced Lung Cancer Patients Treated With Platinum-Based Chemotherapy - Suárez, Gisela María; Catalá, Mauricio; Peña, Yadira; Portela, Susana; Añé-Kourí, Ana Laura; González, Amnely; Lorenzo-Luaces, Patricia; Díaz, Manuel; Molina, María de los A.; Pereira, Karla; Hernández, Jenysbel de la C.; Ramos, Raúl; et al. (Frontiers in Oncology, 2022)
Lung cancer is the second cause of cancer related deaths worldwide. Cancer immunotherapy has evolved with the advances of several forms of treatment, including cancer vaccines, adoptive cell transfer and immune checkpoint inhibitors. However, the molecular heterogeneity in advanced non-small cell lung cancer (NSCLC) makes it difficult not only for diagnosis but also for the management and success is limited to a subset of patients. Chemotherapy and immunotherapy represent the current standard of care for advanced NSCLC. Platinum-based chemotherapy expands the late-differentiated T cell populations. Therefore, immune restoration after chemotherapy to adjuvate the immunotherapeutic potential could be crucial. The aim of this study was to evaluate the effect of Biomodulina T (BT), a thymic polypeptide fraction, on peripheral lymphocyte subpopulations in the context of cancer disease. Additionally, whether these effects might induce a better response to CIMAvax-EGF, an EGF depleting immunotherapy. Eighteen advanced NSCLC patients were evaluated after being treated with platinum-based chemotherapy. We found that the frequency of EMRA CD4+ and CD8+ T cells decreased with the administration of BT, whereas CD4+ naive T cells increase in more than 70% of the patients. Remarkably, CD4+ and CD8+ T lymphocytes expressing PD1 decreased after BT administration. We also found an enhancement of the anti-EGF antibody response with a large percentage of patients treated with CIMAvax-EGF reaching the good antibody response condition after four vaccine doses. Moreover, the median overall survival of patients treated with CIMAvax-EGF was 16.09 months. In conclusion, our results suggest that the immunorestoration generated by the administration of BT after first-line chemotherapy may induce a better immune response to CIMAvax-EGF that could translate into the clinical benefit of patients diagnosed with advanced NSCLC.